2002
DOI: 10.1016/s0002-9440(10)64180-6
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Heterozygosity or Allele Imbalance in Histologically Normal Breast Epithelium Is Distinct from Loss of Heterozygosity or Allele Imbalance in Co-Existing Carcinomas

Abstract: To better understand early steps in human breast carcinogenesis, we examined allele imbalance or loss of heterozygosity (LOH), in co-existing normal-appearing breast epithelium and cancers. We microdissected a total of 173 histologically normal ducts or terminal ductolobular units (TDLUs) and malignant epithelial samples from 18 breast cancer cases, and examined their DNA for LOH at 21 microsatellite markers on 10 chromosome arms. Fourteen of 109 (13%) normal ducts/TDLUs, from 8 of 18 (44%) cases, contained LO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
55
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 31 publications
2
55
0
2
Order By: Relevance
“…These results may also help rationalize prior studies demonstrating genetic abnormalities in normal TDLU epithelium. 37,38 It would be interesting to determine whether the proportion of TDLU with short secretory cell telomeres is increased in women at high risk for breast cancer, such as those with BRCA1 mutations, or decreased in populations at lower risk for breast cancer. Parenthetically, we suspect that most women of reproductive age harbor some TDLU with short secretory cell telomeres, given how frequently we observed focal shortening in the relatively small biopsy samples reviewed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…These results may also help rationalize prior studies demonstrating genetic abnormalities in normal TDLU epithelium. 37,38 It would be interesting to determine whether the proportion of TDLU with short secretory cell telomeres is increased in women at high risk for breast cancer, such as those with BRCA1 mutations, or decreased in populations at lower risk for breast cancer. Parenthetically, we suspect that most women of reproductive age harbor some TDLU with short secretory cell telomeres, given how frequently we observed focal shortening in the relatively small biopsy samples reviewed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…However, instead of tumors, these cancerous cells incorporate into histologically normal ductal structures, respond appropriately to hormones, and even secrete milk proteins [2]. Furthermore, breast epithelial cells with surprisingly abnormal genomes can be found in histologically normal human breast ducts [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Loss of heterozygosity (LOH) or allele imbalances (AI) at various chromosomal loci have been observed in normal tissue adjacent to tumor in breast and bladder cancer patients (Deng et al, 1996;Larson et al, 1998Larson et al, , 2002Lakhani et al, 1999;Forsti et al, 2001;Kurose et al, 2001;Li et al, 2002). Moreover, other studies have reported gene and chromosome alterations in normal tissues, for example TP53 mutations in normal epidermis of patients with non-melanoma skin cancers (Ren et al, 1996) and in histologically normal tissue from the upper aerodigestive tract of cancer patients (Waridel et al, 1997), or cytogenetic abnormalities and growth factor receptor overexpression in normal bronchial epithelium of lung cancer patients (Sozzi et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the importance of normal myoepithelial cells in breast cancer progression has been shown (Hu et al, 2008). These studies proved the existence of alterations in normal tissues of cancer patients and suggested that these alterations might predispose individuals to local recurrence or may belong to the early stages of pathogenesis, in which case, they may suffer further complex and multiple genetic changes during tumor growth (Sozzi et al, 1991;Deng et al, 1996;Ren et al, 1996;Larson et al, 1998Larson et al, , 2002Lakhani et al, 1999;Forsti et al, 2001;Li et al, 2002).…”
Section: Introductionmentioning
confidence: 99%